Performance of hydrostatic and non‐hydrostatic dynamical cores in RegCM4.6 for Indian summer monsoon simulation. (28th May 2020) - Maurya, R. K. S.; Mohanty, M. R.; Sinha, P.; Mohanty, U. C.
Abstract: The efficacy of regional climate model RegCM4.6 using hydrostatic core resolutions at 36km (HY36) and 12km (HY12) and a non‐hydrostatic core resolution at 12km (NH12) is investigated by simulating the normal, excess and deficit monsoon seasons. The ERA‐Interim reanalysis data are used to drive the model and the India Meteorological Department (IMD) and modern‐era retrospective analysis for research and applications (MERRA) rainfall data are used for precipitation verification. The heavy rainfall regions are well simulated in the high‐ compared with the coarse‐resolution simulations, with the maximum in the NH12. The non‐hydrostatic dynamics amalgamate the vertical acceleration with the orographic uplifting that causes more precipitation over hilly regions than that of the hydrostatic core. On the other hand, the lesser precipitation over northwest India is better portrayed in the HY12 than in the other two. Over central India, the HY36 performs better followed by the NH12; and the contrasting precipitation features are also well depicted in the HY36 and NH12. This is probably because of the better representation of large‐scale monsoon features, such as a monsoon trough in the HY36 and local‐scale convective activities in the NH12. Daily rainfall analysis also shows that the high‐resolution model is capable of capturing the active and break phases during the El Niño and La Niña seasons. The non‐hydrostatic model possesses good correlation co‐efficients >0.5 over the hydrostatic model with co‐efficients of 0.35. The analysis of upper air circulations and the derived parameters, including statistical tests, confirm that the RegCM4.6 with non‐hydrostatics is useful for orographic regions, hydrostatic at a coarse resolution and non‐hydrostatic at a finer resolution and could be suitable for plain regions. Abstract : Model domain and elevation (masl) used in the present study.